Cristianismo y pandemia en Argentina. Notas sobre la secularización del discurso religioso - Mauro, Diego; Fabris, Mariano (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The article analyzes the discourse of religious specialists on the pandemic. Throughout the essay we offer some provisional answers based on what happened in Argentina with the authorities of the Catholic Church and the associations of evangelical churches. We defend the hypothesis that the discourse of these religious actors about the pandemic had a low level of enchantment. We also affirm that it was based on a secularized view of society, health and politics, devoid of apocalyptic and conspiratorial perspectives. On the other hand, we affirm that two moments can be demarcated. In the first months, Christian religious institutions supported the government’s health measures. However, in the following months, critical voices emerged demanding more attention to religion in public policy.